Analysis of constant modulus blind equalization algorithms base on "data reuse" - XU Hua1; ZHENG Hui2; ZHANG Dong-mei3 (Tongxin xuebao)
The constant modulus blind equalization algorithm based on "data reuse" could be used to solve the problem of blind equalization of short burst signals,but its important properties hadn’t been studied.The ill-convergence caused by data reuse was analyzed and the restriction was given firstly,and secondly,the conditions of data reuse constant modulus algorithm reaching to the performance of long time signals equalization was analyzed in detail and gave the corresponding results.The validity of these analyses is proved by computer simulation.